Fuzzy set and fuzzy logic (Theory and applications) - George J Klir (Prentice-Hall, 1995)
This book presents theoretical aspects of fuzzy set theory and fuzzy logic and their applications. The book contains an extensive bibliography. It also contains a bibliographical index, name index and subject index